Coulomb crystallites from harmonically confined charged bosons in two dimensions - Mese, A. I. (2008)
We exploit rotational-symmetry breaking in the one-body density to examine the formation of structures in systems of N strongly coupled charged bosons with logarithmic repulsions inside isotropic two-dimensional harmonic traps, with N in the range from 2 to 7. The results serve as a map for ordered arrangements of vortices in a trapped Bose-Einstein condensate. Two types of N-body wavefunctions are assumed: (i) a permanent of N identical Gaussian orbitals centred at variationally determined sites, and (ii) a permanent of N orthogonal orbitals built from harmonic-oscillator energy eigenstates. With increasing coupling strength, the bosons in the orbitals localize into polygonal-ringlike crystalline patterns ('Wigner molecules'), whereas the wavefunctions describe low energy excited states containing delocalized bosons as in supersolid crystallites ('supermolecules'). For N = 2 at strong coupling both states describe a Wigner dimer. © IOP Publishing Ltd.